The impact of omnichannel integrated marketing communications (IMC) on product and retail service satisfaction - Vera Butkouskaya; Olga Oyner; Sergey Kazakov (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This study reviewed three customer-perceived components of integrated marketing communications (IMCs): consistency, interactivity and connectivity, as predictors of positive customer evaluation (product and retail service satisfaction). Design/methodology/approach The customer data from 260 surveys were analysed using structural equation modelling (SEM). The data were collected from the emerging economy in the Moscow region (Russia). Findings The results reported that IMC consistency positively impacts product and service satisfaction. However, the effect of IMC interactivity was only significant in the case of service satisfaction. Meanwhile, IMC connectivity positively influenced only product satisfaction. Research limitations/implications The study contributes to the marketing communications theory by defining three components of omnichannel IMC. It also adds to the customer behaviour theory by confirming the diverse nature of product and service evaluation. This study focuses on the retail industry. Practical implications This research suggests that three components of IMC should be applied together towards enhancing the customer's positive post-purchase evaluation. Meanwhile, consistency enhances product and service satisfaction, interactive impacts satisfaction with the organization and connectivity with the retail service. Originality/value The shift toward omnichannel marketing requires a broader perspective on communication integration. This research reports a novelty result of estimating the separate effect of each component of omnichannel IMC (consistency, interactivity and connectivity) on product and service satisfaction.
Keywords: L81; M31; M37; 330; IMC connectivity; IMC consistency; IMC interactivity; Omnichannel marketing